Experimental Study of The Cooling Effect of Polycrystalline Type PV Panels Using Beeswax - Rusmaryadi, Heriyanto; Khoiri, Muhammad; Sutrisno, Sutrisno; Rachman, Fadhil Fuad; Bizzy, Irwin Fuad (Publikasi Penelitian Terapan dan Kebijakan, 2025)
Indonesia boasts a tropical climate and abundant potential for solar energy year-round, making it an environmentally friendly option. To harness this energy, Photovoltaic (PV) technology is used to convert solar energy into electrical energy. However, one drawback of PV panels is their low efficiency in high temperatures, necessitating the use of passive and active panel cooling methods. While active cooling requires additional power, the passive method offers the advantage of not requiring any extra energy. This study focuses on the passive method, specifically the use of a Phase Change Material (PCM) Beeswax type placed behind the PV panel. The results show that using PCM can increase average efficiency by1.11%, 3.43%, and 2.32%, respectively. Additionally, there was an overall increase in average efficiency of 1.24%, 3.86%, and 2.62%. However, it should be noted that there may be fluctuations in data collection due to uncertain environmental factors.